(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
The performance of geothermal heat extraction in shallow aquifers depends on both Borehole Heat Exchanger (BHE) and soil or aquifer properties. In this work, an analysis of the thermal yield of a shallow geothermal reservoir was made numerically with the finite element method used to simulate heat and mass transfer in the three-dimensional reservoir. The main parameters for analysis which have been considered are the geometry and physical parameters of the BHE and grout, as well as aquifer matrix and groundwater fluid. Physical parameters are thermal conductivity, flow conductivity, expansion coefficient, porosity, volumetric heat capacity, anisotropy and dispersivity. The numerical tests have been performed in single BHE line source configuration representing numerically modelled thermal response test for the estimation of sustainable heat extraction. The domain size was a 100x100 meter rectangle with a depth of 200 meters. Three main lithological configurations have been modelled: gravel aquifer with low and high convection of groundwater fluid, as well as a shallow geothermal reservoir dominated by clay material without convection. For selected cases, the analysis for temporal and spatial discretization was also made. Three-dimensional transient modelling was made in FEFLOW® software with pre- and post-processing done in user-defined Python scripts. The results show the most influential parameters to be considered when setting up the real case simulation of geothermal heating and cooling, as well as optimal temporal and spatial discretization set-up with respect to expected thermal gradients in the reservoir.